2017
DOI: 10.1016/j.clinthera.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cdx2 and TaqI Gene Variants on Vitamin D 3 Modulated Intracellular Chemokine Positive T-Cell Subsets in Pulmonary Tuberculosis

Abstract: This study suggests that vitamin D may regulate the chemokine-positive T cells through the Cdx2 AA and TaqI tt genotypes. This could be helpful to regulate chemokine-mediated inflammatory response during active disease condition. Hence, vitamin D supplementation along with tuberculosis drugs may be useful for faster recovery from the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…Apart from osteoporosis, CdX-2 polymorphism also plays an important role in immune-related conditions. CdX-2 AA is associated with an increased risk for tuberculosis and overall risk for cancer [20,21]. Modulation of transcription activity, as described in previous studies, may explain the findings of our study that revealed the CdX-2 G/A genotype as a potential predictor of IC status.…”
Section: Plos Onesupporting
confidence: 83%
“…Apart from osteoporosis, CdX-2 polymorphism also plays an important role in immune-related conditions. CdX-2 AA is associated with an increased risk for tuberculosis and overall risk for cancer [20,21]. Modulation of transcription activity, as described in previous studies, may explain the findings of our study that revealed the CdX-2 G/A genotype as a potential predictor of IC status.…”
Section: Plos Onesupporting
confidence: 83%
“…Rs11568820 (Cdx2) VDR SNP was not assessed in AITD patients to date (according to the PubMed database, 31.04.2019). This SNP was previously shown to influence the immune system and modify the risk of some infectious diseases (e.g., tuberculosis and rubella) [17, 37, 38]. However, we did not observe a significant association between rs11568820 SNP and AIT risk.…”
Section: Discussioncontrasting
confidence: 94%
“…Nevertheless, no substantial link has been established between this SNP and autoimmune disorders such as T1D, MS, vitiligo, or psoriasis ( Dickinson et al, 2009 ; Zhou et al, 2014 ; Frederiksen et al, 2013 ; Aydıngöz et al, 2012 ). Although it is uncertain why the polymorphism is connected to illnesses like tuberculosis, numerous studies have connected this association to VDR methylation, vitamin D-mediated control of chemokine-positive T cells, and impact adaptive cytokine responses ( Meyer and Bornman, 2018 ; Ovsyannikova et al, 2010 ; Harishankar and Selvaraj, 2017 ).…”
Section: Discussionmentioning
confidence: 99%